Craniofacial disorders in the course of Angelman syndrome - a review of the literature - Katarzyna Brukiewicz; Oskar Komisarek (Kazimierz Wielki University, 2020)
Angelman syndrome is a neurogenetic disorder with an estimated prevalence of 1 in 10.000 to 1 in 40.000 cases. Clinical presentation is based on characteristic neurobehavioral and emotional disorders, a function of the nervous and pulmonary system as well as dysmorphic features within craniofacial and neurocranium. The aim of the study is an evaluation based on the literature reviewing disorders in the craniofacial region in patients with Angelman Syndrome, with particular emphasis on the oral cavity. Literature from the PubMed base and the Main Medical Library from the last 30 years was analysed. sixteen items were obtained; after verification,  the requirements were met by 16 publications, which together contained a description of the craniofacial and oral cavity disorders in 226 patients. Disorders associated with Angelman syndrome affected many aspects related to health, basic life functions and interpersonal relationships. Proper substantive preparation for working with such a patient enables effective prevention and health monitoring, adjustment of the treatment plan, as well as readiness for any unexpected situations.